Are suburethral slings less successful in the elderly? - Alas A. (2017)
© 2016, The International Urogynecological Association. Introduction and hypothesis: We aimed to evaluate the success of suburethral slings in women ≥70 years of age. Methods: This was a retrospective cohort study of women who underwent suburethral sling placement. Subjects were separated into three groups: ≤50 years of age (group 1), 51 to 69 years of age (group 2), and ≥70 years of age (group 3). The primary aim was to evaluate success as defined by ≥ improved on a validated patient improvement satisfaction score and a negative postoperative standardized stress test. Results: There were 1,464 subjects. Mean age was 44.51 ± 4.25 (n = 296) for group 1, 60.5 ± 5.28 (n = 680) for group 2, and 77.68 ± 5.41 (n = 488) for group 3. The median follow-up was 26 (6–498) weeks, 45 (6–498) weeks, and 42 (6–543) weeks, for groups 1, 2, and 3 respectively. Multiple logistic regression analysis demonstrated no difference in sling success according to age stratification. Lower success was associated with having had a previous sling (adjusted OR 0.25, 95 % CI 0.12–0.5), having detrusor overactivity (adjusted OR 0.44, 95 % CI 0.28–0.69), and having a history of urge urinary incontinence (UUI) for ≥ 4 years (adjusted OR 0.54, 95 % CI 0.31–0.95). Conclusions: There is no difference in sling success between the elderly and younger populations. However, those with previous sling surgery or a long standing history of UUI may be at a higher risk of failure.